2008
DOI: 10.1007/s11465-008-0051-0
|View full text |Cite
|
Sign up to set email alerts
|

Noise control technology for generator sets in enclosures

Abstract: Currently, noise pollution is an environmental problem all over the world. The health and life of human beings are affected by loud noise from high power generator sets. To reduce such noise, a sound-attenuated enclosure is widely used for its high performance and convenient usage. By installing equipment in an enclosure, noise is controlled and prevented from radiating. In this paper, noise control techniques for enclosures are presented. Enclosure development trends are predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The results of the outdoor and indoor noise levels associated with the use of generators obtained showed anthropogenic implications of its use above limits set by statutory bodies. The findings of Rao et al (1988);Nailong et al (2008); Fuller et al (2012); Paravathi and Gopalakrishnan (2003) also showed that the use of generator set produced noise levels above permissible limits approved and it exposed the personnel to potential hazards. Also, Nailong et al (2008); Nwaogozie and Owate (200); in their studies found that people can be exposed to noise from different activities that will cause pollution/environmental hazards and medical effects.…”
Section: Comparison Of Noise Levels In Buildings Sampled With the Stamentioning
confidence: 95%
See 1 more Smart Citation
“…The results of the outdoor and indoor noise levels associated with the use of generators obtained showed anthropogenic implications of its use above limits set by statutory bodies. The findings of Rao et al (1988);Nailong et al (2008); Fuller et al (2012); Paravathi and Gopalakrishnan (2003) also showed that the use of generator set produced noise levels above permissible limits approved and it exposed the personnel to potential hazards. Also, Nailong et al (2008); Nwaogozie and Owate (200); in their studies found that people can be exposed to noise from different activities that will cause pollution/environmental hazards and medical effects.…”
Section: Comparison Of Noise Levels In Buildings Sampled With the Stamentioning
confidence: 95%
“…Developed land increased from only 100 ha in 1830 to 12. (Mabogunje, 1968). It is therefore capable of reflecting practices and attributes of the region.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a direct relationship is between industrial noise and the percentage of affected workers, disturbed by noise. Increasing the noise level in the industrial environment also leads to an increase in the number of accidents among workers [4,5,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, high level of noise are considered the most common cause of discomfort and permanent loss of hearing. This is a common and serious problem of the modern industrial world, which can cause hight costs and serious health problems [4,5,15]. Many countries have instituted laws that limit noise exposure of workers in industry [4][5][6]8].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [11] investigates the definition, classification of decoupling motion, together with the necessary condition and several sufficient conditions for mechanism to realize this kind of motion by the use of screw theory. Zhang et al [12] introduced a spherical 3-DoF parallel mechanism, and deduced the necessary and sufficient condition to synthesis full-isotropic parallel mechanism based on the physical meaning of the cow vector of Jacobian matrix.…”
Section: Introductionmentioning
confidence: 99%